Impact Of The Free Trade Agreement (FTA) on Agricultural Product Export Enterprises in Vietnam - Tran, Trang Mai; Nguyen, Anh Viet (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Signing and implementing FTAs, especially new-generation FTAs, has promoted economic growth and improved Vietnamese society's spiritual and material life. Agricultural products are one of the industries most affected by implementing new-generation FTAs. Those impacts include both positive and negative results. This paper will analyze some of the effects of the EU Free Trade Agreement (EVFTA) on agricultural export enterprises in Vietnam after signing the Agreement. From that impact analysis, the paper will offer several recommendations and solutions for businesses and the government to help agricultural export enterprises in Vietnam take full advantage and benefit, also limit the negative impacts of FTAs.